SOSIALISASI AKUNTANSI PESANTREN DALAM PENYUSUNAN LAPORAN KEUANGAN PESANTREN - Soleha, Nurhayati; Yulianto, Agus Sholikhan; Rosiana, Rita; Retnowati, Wulan (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
The financial report of Islamic boarding school (pesantren) has an important role because it is a form of accountability and transparency of public sector organisations. The purpose of this service activity is to provide an understanding of accounting in preparing financial reports in Islamic boarding schools in the district and city of Serang. Partners are six pesantren with students under 500 students. This service was carried out by means of lectures, discussions, practices, and observations. Through this activity, pesantren can increase their insight and knowledge about pesantren accounting and understand the importance of preparing pesantren financial reports based on generally accepted accounting standards (SAK), but in practice they have not used it based on accounting standards (SAK) completely. Keywords: accounting, Islamic boarding school (pesantren), public sector